Antecedents of halal brand personality - Muhamad Fazil, Ahmad (Emerald Group Publishing Ltd., 2015)
Purpose – The purpose of this study is to create and manage halal brands as valuable business assets based on a proposed halal Brand Personality dimension in the micro-spectrum of halalan (lawful) Tayyiba (good) concept in Malaysia. The chances of using Brand personality attributes as a mechanism to get the primary dimensions of halal branding attributes are high. Design/methodology/approach – Methods of interviews and surveys were conducted based on personality traits to construct key dimensions and attributes of the halal Brand Personality. A structured interview with seven halal certification experts from The Malaysian Department of Islamic Development (Jabatan Kemajuan Islam Malaysia – JAKIM) and factor analysis method were based on non-probability, basic sampling using questionnaire surveys on 135 personnel from the Department of Islamic Affairs, Terengganu (Jabatan Hal Ehwal Agama Islam Terengganu, Malaysia – JHEAT) that were involved directly or indirectly in monitoring halal certification. Findings – The author aims to cultivate a theoretical framework for the halal Brand Personality. The paper introduces five dimensions, namely, Purity, Excitement, Safety, Sophistication and Righteousness. Originality/value – The extraction of the five factors that contribute to the halal Brand Personality has been considered to be an assurance and screening process for halal products and services. It embodies values that are not just for Muslims but for everyone.